HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN PELAKSANAAN DIET PADA PASIEN DIABETES MELLITUS - Elang Wibisana; Hyang Wreksagung H; Siti Chotimah (Universitas Mitra Indonesia, 2021)
Diabetes mellitus is a state of chronic hyperglycemia with various metabolic disorders due to hormonal disturbances thar a variety of chronic complications in the eyes, kidney, nerves and blood vessels. Various studies have shown that patient adherence to treatment of chronic disease is generally low. Dietetic therapy is one of the pillars of the control of diabetes mellitus, dietary compliance in carrying out a hope for the hospital healthcare team. The purpose this study is to identify the relationship of knowledge with the implementation od dietary adherence in patient with diabetes mellitus in Poly Deep Disease at General Hospital of Tangerang 2017. The purpose of this research is to know the correlation between the patient diabetes mellitus at general hospital of Tangerang 2017. This reseach is based mainly on descriptive-correlative wich use cross sectional approachment. The sample is 99 respondents that using accidental technical of sumpling as inclusion-exclusion criteria. Using questionnaire technical then. Techniques of data analysis using the chi-square test with significance level α = 0,05. Results showed that knowladge has a relationship with diet adherence with diabetes mellitus obtained chi-square tes p = 0.004 < α = 0,05, which means that HO is rejected. The conclusion of this study that there is a relationship of knowledge with diet adherence in diabetes mellitus in Poly Deep Disease at General Hospital of Tangerang.